Seasonal Variations of Air Quality Measures In Warri and Effurun, Delta State, Nigeria. - Ubaezue U. Egereonu (International Journal of Pollution: Prevention & Control, 2024)
Air quality in Urban Cities like Warri and Effurun has been deteriorating over time. The distribution levels of air pollutants in the Warri and Effurun environments may be related to both natural and man-made factors. In addition to evaluating the quality of rainwater with regard to pH, heavy metals (Fe, Pb, Cd, As, Hg, CU, Zn), and some anions (Cl-, NO3-, SO42-, CO32-), this project study aims to investigate, using standard methods, variations in concentrations of major air criteria pollutants such as carbon monoxide (CO), nitrogen dioxide (NO2), sulphur dioxide (SO2), carbon dioxide (CO2), and total particulate matter. The seasonal air quality was monitored in four major locations each in Effurun and Warri during the rainy and dry seasons from March, 2020 to February, 2021 and the quality of the rain water was assessed during the period of the seasons (March – October for the rainy season and November – February for the dry season). The concentration of the air pollutants was assessed using an automatic digital multi gas tester (Aeroqual Air Tester S200) while the physicochemical properties of the rain water were assessed using appropriate standard methods. The results for the pollutants shows that the concentration of pollutants is higher during the dry season as compared to the rainy season as can be seen that the mean concentration of NO2, SO2, CO, CO2 and TSPM at station E1 in Effurun of 0.018µg/m3, 0.78µg/m3, 0.028µg/m3, 0.0028µg/m3, 128.50µg/m3 during the dry season is higher than that of 0.012µg/m3, 0.25µg/m3, 0.020µg/m3, 0.0018µg/m3, 99.50µg/m3of the rainy season at the same station E1. This trend follows for other stations. Of all the stations monitored station E seems to have the highest concentration of the various pollutants this might be attributed to its proximity to the WRPC where there is a lot of anthropogenic activities there apart from the refinery and the petroleum depot situated there. Apart from the TSPM which had the highest concentration range of 56.35 – 99.50µg/m3 during the rainy season and 78.50– 128.50µg/m3 during the dry season; SO2 among the gaseous pollutants has the highest concentration range of 0.18 – 0.78µg/m3 during the dry season and 0.09–0.25µg/m3 during the rainy season. The concentration range of 0.0027–0.008µg/m3 in the dry season and 0.0012–0.0035µg/m3 in the rainy season for NO2 is the least. The rainwater's physicochemical studies indicate that it has a mean PH value of 6.04, which indicates a slightly acidic content and much more acidic during the months of the dry season than that of the rainy season with the month of January (5.3) most acidic of all the Months. Of all the parameters only Arsenic has no value for any month as the concentration of arsenic was below the instrument detection limit of 0.3 mg/L.
Keywords: Air Pollutants; Air quality; Anthropogenic; Particulate Matter; Warri